Patient satisfaction with healthcare service quality at community health centers - Birry Aasidiqy; Ana Ikhsan Hidayatuloh (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Healthcare service quality is a critical determinant of patient satisfaction, particularly at primary healthcare facilities such as community health centers. Patient satisfaction serves both as an indicator of service success and a reflection of care quality. Purpose: To analysed the relationship between healthcare service quality and patient satisfaction at community health centers. Method: A quantitative cross-sectional study was conducted using total sampling (n = 50 outpatients). Data were collected via a structured SERVQUAL-based questionnaire (tangibles, reliability, responsiveness, assurance, empathy) and a patient satisfaction scale. Bivariate analysis employed the Chi-Square test. Results: A total of 80.0% of respondents rated service quality as good to very good, with empathy (42.0% very good) and assurance (38.0% very good) as the highest-rated dimensions. Overall patient satisfaction reached 82.0% (satisfied to very satisfied). Chi-Square analysis revealed a statistically significant relationship between service quality and patient satisfaction (p = 0.000). Conclusion: Higher healthcare service quality was significantly associated with greater patient satisfaction. Continuous improvement, particularly in physical facilities and service responsiveness, is recommended. Keywords: Healthcare Service Quality; Patient Satisfaction; Primary Healthcare.